2012
DOI: 10.1111/all.12031
|View full text |Cite
|
Sign up to set email alerts
|

Obesity lowers the threshold of allergic sensitization and augments airway eosinophilia in a mouse model of asthma

Abstract: This obesity model demonstrates that HFD-induced obesity lowers the sensitization threshold in a model of asthma. This finding helps to understand why, particularly during childhood, obesity is a risk factor for the development of allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 85 publications
5
35
0
Order By: Relevance
“…In mouse models of allergic airway inflammation, body weight has been correlated with airway eosinophilia, suggesting that obesity may lower the threshold for allergic sensitization and ORIGINAL ARTICLE augment airway eosinophilia (28,29). In contrast, other studies have found no association between body weight and eosinophilia in murine models of asthma (30).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of allergic airway inflammation, body weight has been correlated with airway eosinophilia, suggesting that obesity may lower the threshold for allergic sensitization and ORIGINAL ARTICLE augment airway eosinophilia (28,29). In contrast, other studies have found no association between body weight and eosinophilia in murine models of asthma (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, sensitization to food allergens may have been present in the first year of life, which we did not assess. In mice, obesity lowered the threshold for atopic sensitization, suggesting that obesity causes atopy [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Obesity in mouse models of asthma has been shown to lower the threshold for allergic sensitization, measured by IgE, interleukin (IL)-5, and eosinophilia (47) . Cluster analysis in adults has shown that certain “obese asthmatic” phenotypes have increased IgE (10) .…”
Section: Discussionmentioning
confidence: 99%